Sovereign Mars : transforming our values through space settlement - Haqq-Misra, Jacob (University Press of Kansas, 2023)
"Astrobiologist Jacob Haqq-Misra argues that settling Mars offers humankind a transformative opportunity to avoid the mistakes of the past by "liberating Mars" as a sovereign planet from the start. Rather than see space as a way to escape human problems on Earth, Mars presents humanity with a challenge to address these problems by thinking carefully about the theory and practice of civilization. Drawing on past examples of cooperative sovereignty, such as the Outer Space Treaty of 1967, the Federal Land Policy and Management Act of 1976, and the Antarctic Treaty System, Liberate Mars makes the case for an analogous approach to space that will preserve the space environment and benefit future generations"--